Improving ensemble streamflow forecasts through targeted post-processing and rating curve uncertainty analysis - Askarinejad, Alireza (2024)
Abstract : Flood forecasting plays a pivotal role in effective water resource management and flood risk mitigation. Despite recent advancements, existing ensemble forecasting systems often grapple with issues of unreliability and under-dispersion. The uncertainty in ensemble forecasts can emanate from various sources, including inputs like precipitation, temperature, and streamflow, as well as initial conditions, model structure and parameters, and boundary conditions. Over the past two decades, numerous endeavors have been made to address bias and under-dispersion through the introduction of various statistical post-processing methods in meteorological and hydrological forecasts. However, a significant challenge lies in selecting the appropriate method and strategy in the forecast chain. Limited research has addressed the integration of pre-processing and post-processing in streamflow ensemble forecasting. Moreover, existing studies have generally focused on lumped hydrological models, while the performance of this integration in distributed hydrological models remains scarcely examined. On the other hand, streamflow data, often indirectly measured through rating curves, are particularly susceptible to errors. While various methods have been proposed to estimate rating curve uncertainty (RCU), the impact of RCU on streamflow forecasting system performance remains underexplored. In addition, current post-processing methods utilized in streamflow forecasting systems have disregarded the inherent uncertainty in observational streamflow data. Thus, this thesis delves into the potential and hurdles associated with considering different sources of uncertainty in flood forecasting systems and their impact on system performance. The primary objectives entail 1) assessing and identifying optimal scenarios from pre-processing of both temperature and precipitation and post-processing of streamflow forecasts approaches, or a combination thereof, and 2) evaluating the consideration of rating curve uncertainty on flood forecasting system performance through incorporating into targeted post-processing methodologies. The thesis focuses on a short-range ensemble streamflow forecasting framework spanning lead times of 1 to 5 days for the au Saumon watershed in southern Quebec, Canada. This watershed, being flood-prone, encountered significant challenges during the 2019 and 2017 flood events, including widespread inundation, road closures, and damage to property and infrastructure. Enhancing streamflow ensemble forecasts and upgrading flood forecasting systems holds the potential to greatly benefit decision-makers and the local populace. Chapter 4 (Results part 1), presented as a scientific article, thus delves into assessing and employing various pre- and post-processing strategy scenarios within the flood forecasting framework employing a spatially distributed hydrological model. By applying different statistical processing and bias correction techniques, the performance and quality of ensemble streamflow forecasts were evaluated across different scenarios. The findings highlight biases and under-dispersion as significant factors affecting raw ensemble forecasts. Pre-processing partially improves raw forecasts but doesn't fully address bias in under-dispersed forecasts. Combining pre- and post-processing enhances forecast skill and reliability, albeit with some variations compared to post-processing alone. Integrating flood events into the training dataset and optimizing its length improves the effectiveness of processing methods, underscoring the critical role of data management strategies in enhancing streamflow forecasting systems. Subsequently, Chapter 5 (Results part 2) , evaluates the consideration of rating curve uncertainty, derived from the Voting Point Method (VPM) and Bayesian Rating curve (BaRatin) estimation methods, on the performance of streamflow ensemble forecasts by integrating into a targeted post-processing approach using Weighted Ensemble Dressing (WED) and Cumulative Distribution Function Matching (CDFM) post-processing methods. Post-processing without RCU enhances forecasting system skill and reliability but overlooks the inherent uncertainty in observational data, posing concerns about its effectiveness. Conversely, integrating RCU improves forecast skill, reliability, and effectively addresses observational data uncertainty, offering a notable advantage over traditional post-processing methods. Comparing WED and CDFM post-processing methods highlighted nuanced differences in forecast outcomes, influenced by uncertainty estimation techniques. Both methods showed favorable accuracy metrics, with RCU integration, especially from VPM, notably enhancing forecast quality. However, variations in RCU from different estimation methods may lead to forecast underestimation or overestimation, warranting careful consideration. These findings collectively shed light on the potential and challenges associated with incorporating different sources of uncertainty into flood forecasting systems.
Accepted: 2024-10-15T15:03:35Z Publisher: Université de Sherbrooke

Processus de rétablissement et attachement au lieu dans un contexte de cumul d’inondations : perspective des résident.es d’un quartier socioéconomiquement défavorisé de Gatineau - Hamel, Ariane (Université du Québec en Outaouais, 2024)
Dans la dernière décennie, le Québec a été touché par plusieurs épisodes d’inondations majeures. C’est le cas des communautés riveraines de Pointe-Gatineau, frappées par des inondations historiques en 2017, 2019 et 2023. Depuis, le départ d’une grande partie des riverains de ce quartier socio-économiquement défavorisé et la destruction de plusieurs maisons laissent un grand vide. La présence de nombreux lots vacants amène de l’incertitude parmi les citoyen.nes qui sont resté.es, dans ce qui est considéré comme l’un des plus vieux quartiers de Gatineau (Conseil régional de l'environnement et du développement durable de l'Outaouais, 2021). Bien que ce domaine d’étude soit en émergence, on observe dans la littérature que l’attachement des individus à leur milieu suivant une ou des catastrophes exercerait une influence sur leur processus de rétablissement. Cette étude s’intéresse donc au processus de rétablissement d’individus provenant d’un quartier socioéconomiquement défavorisé qui ont vécu un cumul d’inondations, et au rôle de l’attachement au lieu dans ce processus. Cette recherche mobilise le cadre de désorientation et de réorientation proposé par Cox et Perry (2011) pour expliquer le processus de rétablissement d’individus dans un lieu modifié par un désastre. L’attachement au lieu est conceptualisé en fonction des dimensions recensées par Raymond et ses collègues (2010) et du sentiment d’être chez soi par Cox et Perry (2011). Quatorze personnes sinistrées qui ont vécu les inondations de 2017 et de 2019 dans le quartier de Pointe-Gatineau ont été rencontrées lors d’entrevues individuelles ou familiales en 2023. Parmi ce nombre, neuf demeurent encore dans les communautés riveraines de Pointe-Gatineau, alors que cinq ont quitté le quartier après les inondations de 2019. Les résultats révèlent que l’attachement au lieu joue un rôle prédominant dans le processus de rétablissement des sinistré.es. Selon les participant.es, l’attachement au lieu contribue à l’étape de désorientation ou favorise au contraire la réorientation. Les résultats soulignent en particulier que l’attachement que les participant.es ressentent envers leur domicile et leur environnement naturel et bâti constitue une motivation importante à vouloir demeurer dans le quartier inondable. Par contre, la recherche montre que des facteurs autres que la relation au lieu influencent également le processus de rétablissement, tels que la difficulté à naviguer dans les démarches administratives entourant les programmes d’indemnisation du gouvernement, le fait d’appartenir à un groupe vulnérable, le soutien social et certaines caractéristiques personnelles. De même, l’expérience de vivre plusieurs inondations amène des spécificités qui influencent elles aussi le processus de rétablissement. Les résultats dévoilent notamment des stratégies d’adaptation mises en place par les personnes participantes qui ont décidé de demeurer dans leur quartier. Les stratégies acquises avec l’expérience font en sorte qu’elles se sentent davantage préparées pour des éventuelles inondations. Cette recherche contribue à la littérature émergente qui s’intéresse au processus de rétablissement d’individus touchés par un cumul d’inondations et au rôle de l’attachement au lieu sur ce processus. Elle permet d’offrir des pistes de réflexion aux différents acteurs qui accompagnent les personnes sinistrées avant, pendant et après des inondations et propose des recommandations en ce sens.

Les bonnes pratiques d’interventions psychosociales à adopter lors d’inondation et les facteurs organisationnels favorisant leur bonne marche : point de vue d’intervenantes et d’intervenants de première et deuxième lignes - Maltais, Danielle; Hamel, Ariane; Lansard, Anne-Lise (Reflets, 2024)
En 2017 et en 2019, le Québec a vécu des inondations ayant provoqué d’importants dommages dans plus de 300 municipalités. Ces inondations ont mobilisé un grand nombre d’intervenantes et d’intervenants sociaux et municipaux afin d’assurer la sécurité et le bien-être des personnes sinistrées. Cet article présente le point de vue de ces personnes en lien avec les interventions psychosociales mises en place s’étant avérées efficaces pour atténuer ou prévenir l’apparition de problèmes de santé chez les individus sinistrés, ainsi que les facteurs organisationnels qui ont favorisé leur bon déroulement. Plusieurs types d’intervention psychosociale semblent avoir le potentiel de prévenir la détérioration de l’état de santé et le fonctionnement social des personnes sinistrées, dont l’adoption de l’approche « reaching out » et la mise en place d’équipes dédiées au rétablissement. , The floods that hit the province of Quebec in 2017 and 2019 resulted in significant damage to over 300 municipalities. Many social and municipal stakeholders were mobilized to ensure the safety and well-being of those affected by these floods. This article presents their point of view regarding the psychosocial interventions implemented. Interventions such as these have proven successful in mitigating or preventing health problems among disaster victims, as well as facilitating smooth operations. Psychosocial interventions, such as the “Reaching Out” approach and the creation of dedicated recovery teams, appear to be effective in preventing deterioration in the health status and social functioning of disaster victims.

Projet EPERLAB : Ensemble pour l'étude et la restauration de la rivière Boyer - Rapport final Projet conjoint du programme Odyssée Saint-Laurent du Réseau Québec maritime (RQM) et du programme Affluents Maritime du Regroupement des organismes de Bassins Versants du Québec (ROBVQ) - Biron, Pascale; Michaud, Aubert; Massey, William; Stämpfli, Nicolas; Niang, Mohamed; Lagacé, Robert; Martinelli, Gaetan (2024)
Publisher: [object Object]